Place of work and place of residence informal hiring networks and labor market outcomes - Bayer, Patrick J. 1972-; Ross, Stephen L.; Topa, Giorgio (National Bureau of Economic Research, 2005)
"We use a novel dataset and research design to empirically detect the effect of social interactions among neighbors on labor market outcomes. Specifically, using Census data that characterize residential and employment locations down to the city block, we examine whether individuals residing in the same block are more likely to work together than those in nearby but not identical blocks. We find significant evidence of social interactions: residing on the same versus nearby blocks increases the probability of working together by over 50 percent. We also provide evidence as to which types of matches between individuals result in greater levels of referrals. These findings are robust across various specifications intended to address concerns related to sorting and reverse causation. Further, our estimated match effects have a significant impact on a wide range of labor market outcomes more generally including employment and wages"--National Bureau of Economic Research web site.
Keywords: Gesellschaft; Labor market -- Social aspects -- United States; Neighborhoods -- Economic aspects -- United States; Work -- Social aspects -- United States; USA